Web development with Blazor a practical guide to start building interactive UIs with C# 11 and .NET 7 - Engström, Jimmy (Packt Publishing Ltd., 2023)
Blazor is an essential tool if you want to build interactive web apps without JavaScript, but it has a learning curve. Updated with the latest code in .NET 7 and C# 11 and written by someone who adopted Blazor early, this book will help you overcome the challenges associated with being a beginner with Blazor and teach you the best coding practices. You'll start by learning how to leverage the power of Blazor and exploring the full capabilities of both Blazor Server and Blazor WebAssembly. Then you'll move on to the practical part, centered around a sample project - a blog engine. You'll apply all your newfound knowledge about creating Blazor projects, the inner workings of Razor syntax, validating forms, and creating your own components. This new edition also looks at source generators, dives deeper into Blazor WebAssembly with ahead-of-time, and includes a dedicated new chapter demonstrating how to move components of an existing JavaScript (Angular, React) or MVC-based website to Blazor or combine the two. You'll also see how to use Blazor (Hybrid) together with .NET MAUI to create cross-platform desktop and mobile applications. When you reach the end of this book, you'll have the confidence you need to create and deploy production-ready Blazor applications, and you'll have a big-picture view of the Blazor landscape.
Includes bibliographical references and index
Keywords: Microsoft .NET Framework; Web applications -- Development; Application software; C# (Computer program language); Applications Web; Développement; Logiciels d'application; C# (Langage de programmation)